Beyond numbers: the participation of indigenous peoples in parliament - Inter-Parliamentary Union; Inter-Parliamentary Union
This report examines the extent to which indigenous peoples are participating meaningfully in external decision-making processes through parliamentary structures. It is based on a survey of countries known to have indigenous populations (26 of 77 parliaments participated), as well as on secondary data for another 10 parliaments.1 Because of the relatively limited data available, the report seeks not to quantify, but to provide a deeper understanding of indigenous peoples’ participation in parliaments. It analyzes the data against other research findings about their political participation as well as external variables, such as the kind of electoral system in place in each country.